Pengaruh Profitabilitas, Struktur Aktiva, Ukuran Perusahaan dan Kebijakan Dividen terhadap Struktur Modal : (Studi Empiris pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2023) - Vina Lestari; Retno Fuji Oktaviani (Pajak dan Manajemen Keuangan, 2024)
This study aims to determine the effect of profitability, asset structure, company size and dividend policy on capital structure (empirical study on food and beverage subsector companies listed on the Indonesia Stock Exchange for the 2018-2023 period). The type of data used in this study is secondary data obtained from documentation in the form of financial statements of Food and Beverage companies. The total population in this study was 95 companies, sample selection was carried out by the Purposive Sampling method. So that a sample of 19 companies was obtained, the independent variables used were Profitability, Asset Structure, Company Size and Dividend Policy, the dependent variable used was Capital Structure. Data analysis was carried out quantitatively and the analysis methods used in this study were in the form of multiple linear regression and classical assumption tests including normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Data testing in this study used Statistical Package for Social (SPSS) Version 25.0. The results showed that Profitability had a significant negative effect on Capital Structure, Company Size had a significant positive effect on Capital Structure, while Asset Structure and Dividend Policy did not affect Capital Structure.